Praktik Permainan Mesin Capit Manusia (Human Claw Machine) dalam Pandangan Hukum Islam dan Maqashid Syariah: Human Claw Machine Game Practices from the View of Islamic Law and Maqashid Syariah - Antiek Firdausi Putri (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2024)
The human claw machine game is an innovative model of the doll claw machine game. The problems arising from this contemporary phenomenon are related to applicable law. In the human claw machine game, the laws of the game and the form of transactions used are not yet clearly known. The aim of this research is to explore the laws of human claw machine games from the perspective of Islamic law and maqashid sharia. The research method used in this research is normative legal research which will examine legal issues with the provisions in the Al-Qur'an and hadith. The results of the analysis show that the law of human claw machine games when viewed from a gaming perspective is a form of game that is prohibited because it contains elements of chance and speculation which are similar to qimar. Meanwhile, as a business tool, this game is a form of buying and selling transaction that contains elements of gharar and maysir. The position of maqashid sharia in the practice of human claw machine games includes two main things, namely the protection of reason and wealth.